(untitled) (KMC Journal, 2024)
Exploring the quality of communication materials from the perspectives of the target audiences is essential for the effectiveness of HIV and AIDS prevention programmes. In this context, a descriptive phenomenological study was carried out in Banke district of Nepal to explore the audiences’ perceptions of the quality of HIV and AIDS-related communication materials. In-depth interviews were carried out with nine participants selected through snowball sampling from sexual minority people and female sex workers. The participants were partially satisfied with the quality of the communication materials from the perspectives of attractiveness, credibility, empowerment, practical application, behaviour change and privacy. They were not satisfied with their quality from the perspectives of readability, sufficiency, comprehensibility and access. This study suggests that communication materials including precise and illustrative messages with familiar pictures, symbols and language should be easily available to the audiences maintaining privacy.